2012
DOI: 10.1002/aoc.2877
|View full text |Cite
|
Sign up to set email alerts
|

1‐(α‐Aminobenzyl)‐2‐naphthol as phosphine‐free ligand for Pd‐catalyzed Suzuki and one‐pot Wittig‐Suzuki reaction

Abstract: Air stable and easily accessible, 1-(a-aminobenzyl)-2-naphthols are used as efficient phosphine-free ligands in palladiumcatalyzed Suzuki reaction for a variety of substrates under conventional heating as well as ultrasonic conditions. Multibrominated aromatic substrates were successfully converted to corresponding arylated moieties with good conversion and selectivity. A novel one-pot two-step cascade reaction strategy involving Wittig and Suzuki reactions is developed for efficient synthesis of 4-styryl biph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 148 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…Recently there has been a growth of interest in one‐pot syntheses or processes of performing many chemical steps in tandem to produce useful molecules . As a part of our ongoing efforts we have recently reported a few variations of one‐pot procedures for the synthesis of functionalized conjugated molecules from readily available starting materials . One of the key components of the Mizoroki–Heck reaction is an electron‐deficient alkene, commonly a styrene derivative.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently there has been a growth of interest in one‐pot syntheses or processes of performing many chemical steps in tandem to produce useful molecules . As a part of our ongoing efforts we have recently reported a few variations of one‐pot procedures for the synthesis of functionalized conjugated molecules from readily available starting materials . One of the key components of the Mizoroki–Heck reaction is an electron‐deficient alkene, commonly a styrene derivative.…”
Section: Resultsmentioning
confidence: 99%
“…In the second set of one‐pot reactions, we explored the combination of Wittig and Suzuki–Miyaura reactions as the two reaction components . In the first stage the olefin is synthesized by Wittig reaction of aromatic aldehyde and the Wittig phosphonium salt of 4‐bromobenzyl bromide.…”
Section: Resultsmentioning
confidence: 99%
“…Often, the oxidant of choice is MnO 2 [40,[43][44][45][46][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97], although a number of reactions are known where transformations were carried with air oxygen using metals and metal oxides as catalysts [72][73][74][75][76][77][78]. As many Wittig-and HWE reactions tolerate metal catalysts, this allows the running of Wittig/HWE reactions in combination with metal catalyzed cross coupling reactions and olefinations such as Heck [114][115][116][117][118][119][120][121][122][123], Suzuki [111][112][113], Sonogashira [119][120]…”
Section: Resultsmentioning
confidence: 99%
“…Wittig-and Horner-Wadsworth-Emmons reactions can be combined with C─C-coupling reactions such as Suzuki cross-coupling [111][112][113], Mizoroki-Heck reaction [113][114][115][116][117][118] and Sonogashira-reaction [119]. Initially, it was observed that conjugated phosphoranes were stable under reaction conditions used for Heck-or Suzuki reactions (Scheme 9).…”
Section: Wittig-and Hwe Reactions and C─c-coupling Reactions In One-pmentioning
confidence: 99%
“…Not quite rigidly classifying the transformation as a homogenous or heterogeneous process, they preferred to postulate that different active catalytic species (cocktail of compounds) were present in solution. A series of 1-(α-aminobenzyl)-2-naphthols have been prepared, by Chaudhary and Bedekar, [140] from 2-naphthols using an aromatic Mannich reaction [141] and screened as air-stable phosphine-free ligands for Pd-catalyzed US assisted SMC. The amino phenol structure, as reported in Figure 13, has a suitable arrangement of heteroatoms to form a six-membered stable chelate, a prerequisite for use as a ligand in metal-catalyzed reactions.…”
Section: Ultrasound-assisted Smc Reactionsmentioning
confidence: 99%